Razão triglicérides/HDL-C e proteína C reativa de alta sensibilidade na avaliação do risco cardiovascular - Vieira, Eder Andrade; Carvalho, Wilson Andrade [UNESP]; Júnior, Roque Aras; Couto, Fábio David; Couto, Ricardo David (FapUNIFESP (SciELO), 2011)
Introduction: Calculated indexes from laboratory measurements and the determination of plasma markers are commonly used in cardiovascular risk assessment. Objective: To use triglycerides/high-density lipoprotein cholesterol (HDL-C) ratio, estimate of low-density lipoprotein (LDL) particle size and high sensitive C-reactive protein (hs-CRP) levels to the clinical and laboratorial assessment of coronary risk among patients with coronary disease. Material and methods: Sixty patients were chosen accordingly, 36 female (F) (65 ± 9 years of age) and 24 male (M) (55 ± 10 years of age) diagnosed with stable ischemic cardiopathy at Ana Neri Hospital, Salvador, Bahia, Brazil. The investigation was carried out at the Clinical Biochemistry Laboratory of the College of Pharmacy at Federal University of Bahia (UFBA). Blood samples were collected after a 12-hour fast to determine hs-CRP, lipid profile and risk indicators. All data were assessed through Syncron LX®20 Beckman Coulter. The inferential analysis results were considered significant when p ≤ 5%. Data analysis was carried out with GraphPad Prism® (4.03 version) software. Results: Data analysis showed a positive correlation between hs-CRP and triglycerides/HDL-C ratio only among women (r = 0.4; p = 0.0442), n = 36. The analysis of other parameters did not show any significance. Conclusion: The triglycerides/HDL-C ratio and hs-CRP may be used as indicators of increase in cardiovascular risk among women with coronary artery disease (CAD).
Triglycerides/HDL-C ratio and high sensible C-reactive protein to the evaluation of cardiovascular risk
Keywords: Coronary artery disease; Risk estimates; Sensible C-reactive protein